Performance Management Systems (PMS): Challages and Opportunities in the Public Sector - Xolani Thusi; Nokukhanya N Jili; Toyin C Adetiba; Victor H Mlambo; Nkosingiphile Mkhize (Brawijaya University, 2023)
To the vast majority of scholar’s public institutions should have effective and efficient Performance Management Systems (PMS) in place to promote and develop the performance of civil servants. In the public sector, good management of staff performance is fundamental to efficient service delivery. The mandate of public institutions is to offer quality and effective service delivery to the public; as a result, public institutions' performance is scrutinized by the public, who have higher expectations from the government. These expectations are based on the votes cast and the taxes paid by the general public. Thus, public institutions should monitor and enhance each employee's performance and productivity to ensure the efficient provision of public services. This article seeks to analyse the challenges encountered by public sector in executing PMS and suggest the strategies the public sector can use to enhance staff performance.